Pro SQL Server 2008 Mirroring - Davis, Robert L. (Apress, 2011)
Pro SQL Server 2008 Mirroring is part of Apress’ two-pronged approach to high-availability in the SQL Server space. It is a focused and deep book on mirroring that perfectly complements Apress’ upcoming book no failover clustering. Taken together, the combination of Pro SQL Server 2008 Mirroring and Pro SQL Server 2008 Failover Clustering deliver the deepest and most authoritative content for those charged with the stressful and demanding task of ensuring that their SQL Server databases are up and running all of the time, no matter what.